Numerical investigation on the bearing capacity of RC columns strengthened by HPFL-BSP under combined loadings. (July 2021) - Huang, Hua; Guo, Mengxue; Zhang, Wei; Zeng, Jie; Yang, Kun; Bai, Hao
Abstract: To study the effect of the axial compression ratio, torsion-bending ratio, and eccentricity on the mechanical performance of reinforced concrete (RC) columns under combined loadings, the numerical analysis is implemented based on ABAQUS and agrees well with the experimental results. The bearing capacity increased with the increase of the axial compression ratio, but the energy dissipation and ductility decreased. The bearing capacity and stiffness are degraded with the increase of the torsion-bending ratio. When the eccentricity increased from 0.125 to 0.25, the numerical results show the poor seismic performance. The results show that loading methods affected the mechanical performance, and the negative effect of the torque is noticeable. Moreover, the unified bearing capacity of RC columns under combined torsion is calculated by the modified existing Park & Ang failure criterion. Highlights: Numerical analysis for investigating the bearing capacity is implemented. The bearing capacity increases with the increase of the axial compression ratio. The bearing capacity and stiffness degrade with the increase of the torsion-bending ratio. The loading methods have an negative effect of the torque.